Navigating the shadows: medical professionals’ values and perspectives on end-of-life care within pediatric intensive care units in Croatia - Curkovic, Marko; Rubic, Filip; Jozepovic, Ana; Novak, Milivoj; Filipovic-Grcic, Boris; Mestrovic, Julije; Lah Tomulic, Kristina; Peter, Branimir; Spoljar, Diana; Grosek, Štefan; Janković, Sunčana; Vukovic, Jurica; et al. (Frontiers in Pediatrics, 2024)
Background and aim This study explores healthcare professionals’ perspectives on end-of-life care in pediatric intensive care units (ICUs) in Croatia, aiming to illuminate their experiences with such practices, underlying attitudes, and major decision-making considerations. Amid the high variability, complexity, and emotional intensity of pediatric end-of-life decisions and practices, understanding these perspectives is crucial for improving care and policies. Methods The study utilized a cross-sectional survey intended for physicians and nurses across all pediatric ICUs in Croatia. It included healthcare professionals from six neonatal and four pediatric ICUs in total. As the data from neonatal and pediatric ICUs were examined jointly, the term pediatric ICU was used to denominate both types of ICUs. A statistical analysis was performed using Python and JASP, focusing on professional roles, professional experience, and regional differences. Results The study included a total of 103 participants (with an overall response rate—in relation to the whole target population—of 48% for physicians and 29% for nurses). The survey revealed diverse attitudes toward and experiences with various aspects of end-of-life care, with a significant portion of healthcare professionals indicating infrequent involvement in life-sustaining treatment (LST) limitation discussions and decisions, as well as somewhat ambiguous attitudes regarding such practices. Notably, discrepancies emerged between different professional roles and, in particular, regions, underscoring the high variability of LST limitation-related procedures. Conclusions The findings highlight a pressing need for more straightforward guidelines, legal frameworks, support mechanisms, and communication strategies to navigate the complex terrain of rather burdensome end-of-life pediatric care, which is intrinsically loaded with profound ethical quandaries.